Learning to read critically in teaching and learning - Poulson, Louise; Wallace, Mike, 1950- (London : SAGE, 2004)
Combining a teaching text with exemplary reports of research and a literature review conducted by international scholars this collection addresses the critical analysis of texts and the methods used to incorporate such analysis into literature reviews.
Critical reading for self-critical writing -- Designing and writing about research : developing a critical frame of mind -- Changing instructional and assessment practices though professional development -- Learning from homework : a case study -- An inquiry into the moral dimensions of teaching -- Investigating formative classroom assessment -- Participation and control in learning : a pedagogic democratic right? -- Primary school teachers' theoretical beliefs about literacy : an exploratory study -- Promoting inclusive education : a review of literature on teachers' attitudes towards integration and inclusion.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Education -- Research; Teaching -- Research; Learning -- Research; Criticism; Apprentissage -- Recherche; Critique; EDUCATION -- Research; Criticism; Education -- Research; Learning -- Research; Teaching -- Research; Kritisches Denken; Lesen; Unterricht; Wissenschaftliche Literatur; Literatuuronderzoek; Onderwijskunde